Austempering heat treatment in ductile iron with niobium and chromium additions Tratamento térmico de austêmpera em ferro fundido nodular com adições de nióbio e de cromo - Pimentel A.S.O.* (2017)
© 2017, Universidade Federal do Rio de Janeiro. All rights reserved.The austempered ductile iron (ADI) finds applications in abrasive wear resistant parts. CADI (Carbidic Aus-tempered Ductile Iron) is one type of ADI, which contains free eutectic carbides in its microstructure. The addition of niobium in ductile iron also results in the formation of carbides, but harder and more stable than the CADI carbides. Macro additions of niobium are promising. The present work studied the influence of the addition of niobium in the austempering treatment. Five different compositions, ductile iron, ductile iron with chromium and ductile iron with three niobium additions, were austempered at two temperatures for five different times. The retained austenite were estimated by metallography. The addition of niobium caused the formation of primary polygonal carbides while the addition of chromium caused the formation of carbides of dendritic morphology in intercellular regions. The results shows that the additions of niobium and, more intensively, of chromium result in the increasing of the retained austenite content. The additions also affect the morphology of the ausferritic microstructure.